Spare tyres with a hole: Investment funds under stress and credit to firms - Giulio Nicoletti; Judit Rariga; Costanza Rodriguez D'Acri (European Central Bank (ECB), 2024)
We study the impact of a liquidity shock affecting investment funds on the financing conditions of firms. The abrupt liquidity needs of investment funds, triggered by the outbreak of the Covid-19 pandemic, prompted a retrenchment from bond purchases of firms and a withdrawal of short term funds from banks, impacting firm financing costs directly via bond markets, and indirectly via banks. According to our results, the spreads of corporate bonds held by investment funds increased. Furthermore, an increase in the short term funding exposure of a bank to investment funds triggered a contraction in new loans to euro area firms. Overall, our results show that while non-banks in general support firm financing by acting as a spare tyre when banks do not, their own stress can trigger a contractionary credit supply effect for firms.
Keywords: E52; G23; G30; 330; Firm financing; Investment funds; Bank lending channel; Bond lending channel; Monetary policy